2004
DOI: 10.1021/ja047557p
|View full text |Cite
|
Sign up to set email alerts
|

Protein Surface-Assisted Enhancement in the Binding Affinity of an Inhibitor for Recombinant Human Carbonic Anhydrase-II

Abstract: We elaborate on a novel strategy for enhancing the binding affinity of an active-site directed inhibitor by attaching a tether group, designed to interact with the surface-exposed histidine residue(s) of enzymes. In this approach, we have utilized the recombinant form of human carbonic anhydrase-II (hCA-II) as the enzyme source and benzenesulfonamide and its derivatives as inhibitors. The steady-state kinetic and the ligand binding data revealed that the attachment of iminodiacetate (IDA)-Cu(2+) to benzenesulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 42 publications
4
57
1
Order By: Relevance
“…Due to the fact that Eu 3+ exhibits a fairly weak affinity for Ec MetAP (Figures 2 and 4) as compared to most other metal ions, we could analyze the overall binding isotherm by a complete solution of quadratic (rather than cubic) equation (Eq. 2) as previously described [11]. The solid smooth lines are the best fit of the data for the apparent K d values of the enzyme-Ca 2+ and Fe 3+ complexes as being equal to 1.6 and 0.6 µM, respectively.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Due to the fact that Eu 3+ exhibits a fairly weak affinity for Ec MetAP (Figures 2 and 4) as compared to most other metal ions, we could analyze the overall binding isotherm by a complete solution of quadratic (rather than cubic) equation (Eq. 2) as previously described [11]. The solid smooth lines are the best fit of the data for the apparent K d values of the enzyme-Ca 2+ and Fe 3+ complexes as being equal to 1.6 and 0.6 µM, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…The data were analyzed by a modified form of the competitive binding model of Eq. 2 as described by Banerjee et al [11]: L=true(true(normalLnormalc[normalEnormalt]true)*[normalEnormalt]true([Et]+[M]+Kd+true(Kd[Eu]Kdtrue)true)true([Et]+[M]+Kd+true(Kd[Eu]Kdtrue)true)24[Et][M]2true)+offset Where L c is the total change in luminescence signal (L) upon complete displacement of Eu 3+ from the active site, [E t] , [M] and [Eu] are the concentrations of the enzyme, the displacing metal ion, and Eu 3+ respectively, while K d and K d ’ are the dissociation constants of displacing metal ion and Eu 3+ respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this context it can be included also a recent study of Srivastava and co-workers, where the derivatization of 12 with a functional group supposed to interact with the surface exposed His residues of the CA enzymes, 124,125,130 has allowed to obtain very strong CA inhibitors of type 19 and 20. 124,125 In these molecules the benzenesulfonamide is conjugated to the iminodiacetate-Cu 2+ (IDA-Cu…”
mentioning
confidence: 99%
“…Simple molecules such as benzenesulfonamide bind to human carbonic anhydrase I (hCA-I) with low-micromolar affinity [48]. Researchers at North Dakota State University in Fargo found that they could enhance this affinity by two orders of magnitude by making "twoprong" inhibitors [49] containing both a benzenesulfonamide moiety and an iminodiacetate (IDA) moiety; this molecule only shows increased potency in the presence of copper (II) and the authors argue that this is due to the coordination of copper by surface histidine residues and the IDA functionality [48,50].…”
Section: Metal-mediatedmentioning
confidence: 99%